A nano‐plasmonic chip for simultaneous sensing with dual‐resonance surface‐enhanced Raman scattering and localized surface plasmon resonance. Issue 4 (27th March 2014) - Lin, Jiao; Zhang, Yuan; Qian, Jun; He, Sailing; He, Sailing; Zhou, Bingkun
<x xml:space="preserve">Abstract</x> A dual‐resonance surface‐enhanced Raman scattering (SERS) chip which also serves as a localized surface plasmon resonance (LSPR) refractive index sensor is proposed. The dual‐resonance SERS chip can simultaneously enhance excitation and Stokes lines for Raman signals detection in a broad wavelength region with virtually no limitation. Thus, it is especially useful for Raman detection at long wave numbers and hyper Raman. The great performance of this chip relies on the highly independent tunability of the two localized plasmonic resonances from the optical to the near‐infrared region and the strict "hot spot" match in space for both resonant wavelengths. Furthermore, Raman signals of poly‐methyl‐methacrylate (PMMA) from 500 cm−1 to 3300 cm−1 are measured in the experiments and an obvious superiority can be seen compared to a single‐resonance SERS chip. In an addition, by using the subradiant magnetic dipole resonance, the LSPR refractive sensor gives a high sensitivity of 577 nm/RIU and high figure of merit (FoM) of 14.2. The experimental results are consistent with the simulated results. This dual‐functional sensing chip opens a route for dual‐modality detection of the concentration of some specific molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>